Remarks on the approximation of a M|G|? queue system by a Markov renewal process - Ferreira, M. A. M. (Journal of Mathematics and Technology, 2014)
It is presented a Markov renewal process, suggested in (1, 2) as a tool to obtain good approximations for the M|G|? queue interesting parameters.